The Construction of the Pedagogic Political Project: Contributions of Collaborative Action Research - Dirléia Fanfa Sarmento; Cledes Antônio Casagrande (Arizona State University, 2015)
The text analyses the constitutive process of the Pedagogical Political Project (PPP) of a City Department of Education located in the State of Rio Grande do Sul (Brazil), emphasizing the contributions of the collaborative action research while posture that feeds the political commitment, the critical thinking and cooperative relations for the establishment of learning communities. It articulates the reflections from a meta-analysis of the analytical investigative process itself with the constitution of this Project, having as protagonists the education professionals who work at the Department of Education. The findings (arising from the analysis of the content of documents, of records of observations of the formative meetings in the Field Journal and of the interviews) signal to the following contributions of collaborative action research for the process in focus: a) the empowerment and the role of the subjects involved in the construction of the PPP; b) the reflection on the praxis itself; c) the (re) construction of concepts and the revision of concepts through research-action-training; d) the possibility of a further incursion of the investigated phenomenon in so far as it gives continuity to the movement typical spiraled research-action. We highlight the issue of time of the research, because when we crave for transformations, it requires a long and constant process of reflection-action-criticism. Thus, the impacts arising from the action research are not immediate, but expected over time. Such impacts can become a source of generating new investigations.